The legal framework for protecting the rights of employment of persons with disabilities in Malaysia: a comparative study between Malaysia and the United Kingdom / Asmahani Amiruddin … [et al] - Amiruddin, Asmahani; Mohd Yunus, Abd Shukor; Zainudin, Intan Syarafina; Che Wan Raksan, Wan Hajaratul Rafzan (Faculty of Law, 2012)
Among the social issues that are being overlooked by the society is regarding the persons with disabilities (PWD) in our community. This group of people are commonly being discriminated either directly or indirectly in every aspects of their life especially in regards of employment. It is a must, to ensure that they are being seen as an equal as other normal citizens, protected by laws and policies. In Malaysia, there are laws which govern matters in protecting the rights of the PWD that are the Persons with Disabilities Act 2008 and Article 8(2) of Federal Constitution 1963. However, these statutes have yet to achieve its objectives in protecting the rights of the disabled. Therefore, the Persons with Disabilities Act 2008 and Article 8(2) of Federal Constitution 1963 are referred to in this study, to find the lacuna as well as opportunities on which part of employment sector does available for the service of the PWD in our country. The purpose which is clear upon us within this study is to reveal the gap in the existing law and knowledge to provide improvement better opportunities as well as to ensure that the rights of employment of the PWDare protected. In addition to that, in order to provide a comparative analysis of the study, the law on rights of employment of the PWD under Equality Act 2010 in the United Kingdom will be critically examined and its application will be reviewed and compared to Malaysian Persons with Disabilities Act 2008. We will look on how the enforcement of this particular law in the United Kingdom could assist us in Malaysia in determining and comparing what is the best treatment should be given to the PWD in our community in regards of employment in both public and private sector. It is our responsibility, the government, as well as the society, to take a good care of these people. This is an obligation if we wish to achieve "developed" status within this few years and to be achieve zero unemployment is a need towards achieving developed nation.